RANCANG BANGUN AUDIO AMPLIFIER DENGAN MENGGUNAKAN MOSTER SEBAGAI KOMPONEN UTAMA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MAHASISWA - Nehru, Nehru; Saputra, Oki (EduFisika: Jurnal Pendidikan Fisika, 2021)
This study aims to determine the understanding of students' concepts on the basic material of electronics based on the project based learning model. This research is a design research. The research sample was 35 electrical engineering students. Data collection is in the form of a concept understanding test. Based on the results of research and discussion, it can be concluded that project based learning can improve students' understanding of concepts in basic electronics courses, but is still in the moderate category.